Pusat Kajian Dan Kebudayaan Lingga Dengan Pendekatan Arsitektur Neo Vernacular - Firdiansyah, Robby; Susilawati, Mira Dharma; Firzal, Yohannes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Lingga is one of the relics of the Islamic kingdom that was founded around 1828 AD until 1911 AD. There are also have many historical and cultural relics in Lingga. Nowadays, many people are ignorant of history and culture in Lingga, this causing the culture and history of land to begin to be eliminated from the community. Therefore a design of recreational areas for learning and cultural development is needed, so that people can improve their knowledge about cultural historys of Lingga. In addition, the design of this area is useful for historians and historians to study and develop the culture in Lingga. As for the method used in this design is to use the Neo-Vernacular Architecture approach by applying the principles and design ideas that exist in Malay Lingga house with the addition of modern elements in it. The concept used is the transformation of the Nature and Culture of Lingga combined with the theme of Neo Vernacular architecture design, expected to produce a form of display of building in a new form but still maintain the existence of local culture and unite the architecture with aspects of Linga culture and nature. Keywords: Research, Culture Centre, Lingga, Neo Vernacular.